Alternative learning media post-covid-19: uncertainty reduction theory perspective - Mujiono; Daniel Susilo (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
This study aims to determine how users respond to the use of social media during online learning after the COVID-19 pandemic from the perspective of uncertainty reduction theory. This study uses a phenomenological research method, where data collection is carried out by means of Focus Group Discussion (FGD), which was conducted twice on 15 users of online learning applications. Through this research, it is known that the user's response from the compulsion in using the online learning model is that the subject tends to feel mostly bored, difficult to discipline, tendency to be lazy, and has the proclivity to be dishonest. In addition, in terms of emotional connection, teachers and students do not have a good bond, which is far different when using the offline learning modality. The majority of users prefer to utilize the offline learning system when the pandemic ends. One person prefers to use a hybrid system which is a combination of online and offline learning method.